Carbon encapsulated Fe3O4/graphene framework with oriented macropores for lithium ion battery anode with enhanced cycling stability. Issue 119 (17th November 2015) - Han, Sheng; Wang, Xinjing; Huang, Yanshan; Tang, Yanping; Ai, Yani; Jiang, Jianzhong; Wu, Dongqing
Abstract : Carbon encapsulated Fe3 O4 /graphene frameworks (C-Fe3 O4 /G) with highly oriented macropores show good rate capability and improve the cycle stability when used as anode material for LIBs. Abstract : Carbon encapsulated Fe3 O4 /graphene frameworks with highly oriented macroporous structures have been constructed by an ice-segregation-induced self-assembly process. Serving as the anode materials in lithium-ion batteries, the oriented macropores can reduce the polarization of electrode and the loss of capacity, and the carbon shells can effectively prevent the pulverization of Fe3 O4 caused by the inner-plane volume expansion. C-Fe3 O4 /G with 60 wt% of Fe3 O4 delivers a high capacity of 1065 mA h g −1 at a current density of 0.2 A g −1 after 200 cycles. Even at a high current density of 8 A g −1, the electrode still achieves a high capacity of 470 mA h g −1 .